A comparison of preoperative and postoperative anxiety levels affecting preoperative and postoperative processes of orthopedics patients - Engin, Muhammed Cagatay; Toy, Serdar; Cenk Turgut, Mehmet (Annals of Medical Research, 2022)
Aim: Different anxiety levels come up and many of the patients become worried before operations. If there was anxiety, the patients should be relieved by diagnosing, and the negative anxiety should be turned into a positive form. It will cause positive reactions of the patients and make the treatment gains increase. We aimed to compare the anxiety levels of the patients about the orthopedic operations according to the sex, age, and education levels of the patients.Materials and Methods: 122 patients who underwent knee arthroscopy under spinal anesthesia in the Orthopedics and Traumatology operating room were included in the study. Patients aged between 18 and 55 years, included in ASA I and II classes, literate, not having any psychiatric and neurological problems, not using psychiatric drugs, and not using chronic alcohol, were included in the study. The patients’ anxiety levels were checked before and after surgery using the “State-Trait Anxiety Inventory Test (STAI TX-1 Anxiety Skala)”.Results: It was found that there was no significant difference between the patients’ pre and post-test state anxiety levels; however, the post-tests put forward that the patients’ state anxiety levels after the operation were a little higher than their pre-tests’ state anxiety levels before the operations.Conclusion: The patients should be informed about the problems, limitations, advantages, and disadvantages of the operation before and after the procedure. The patients should also be given psychological support to decrease their anxieties about the surgical procedure.
Keywords: Anxiety; arthroscopy; orthopedics; scale; test